DNIT - A new approach for design pattern detection - Pande A.; Gupta M.; Tripathi A.K. (My University, 2025)
In many object oriented softwares, there are recurring patterns of classes. With the help of these patterns specific design problem can be solved and object oriented design becomes more flexible and reusable. Design Pattern Detection is a part of solutions to Software Engineering difficulties. Mining of design pattern instances is important for program understanding and software maintenance. Hence a reliable design pattern mining is required. Here we are introducing a new method called DNIT (Depth-Node-Input Table) for design pattern detection, which extracts the design patterns which exists at different depths in the rooted directed graph of system under study. ©2010 IEEE.